Fluid mechanical performance of ureteral stents: The role of side hole and lumen size - Shaokai Zheng; Dominik Obrist; Fiona Burkhard; Francesco Clavica (Wiley, 2023)
Abstract Ureteral stents are indispensable devices in urological practice to maintain and reinstate the drainage of urine in the upper urinary tract. Most ureteral stents feature openings in the stent wall, referred to as side holes (SHs), which are designed to facilitate urine flux in and out of the stent lumen. However, systematic discussions on the role of SH and stent lumen size in regulating flux and shear stress levels are still lacking. In this study, we leveraged both experimental and numerical methods, using microscopic‐Particle Image Velocimetry and Computational Fluid Dynamic models, respectively, to explore the influence of varying SH and lumen diameters. Our results showed that by reducing the SH diameter from 1.1 to 0.4mm the median wall shear stress levels of the SHs near the ureteropelvic junction and ureterovesical junction increased by over 150%, even though the flux magnitudes through these SH decreased by about 40%. All other SHs were associated with low flux and low shear stress levels. Reducing the stent lumen diameter significantly impeded the luminal flow and the flux through SHs. By means of zero‐dimensional models and scaling relations, we summarized previous findings on the subject and argued that the design of stent inlet/outlet is key in regulating the flow characteristics described above. Finally, we offered some clinically relevant input in terms of choosing the right stent for the right patient.